2018
DOI: 10.1007/s13202-018-0555-z
|View full text |Cite
|
Sign up to set email alerts
|

Transient model analysis of gas flow behavior for a multi-fractured horizontal well incorporating stress-sensitive permeability

Abstract: The assumption of constant reservoir permeability is not strictly applicable to reservoirs where rock properties undergo changes, such as stress-sensitive porous media. Most researches on the permeability stress sensitivity mainly concentrated on experimental approach, physical modeling or pressure transient analysis, whereas rate transient analysis does not attract much attention. Based on source/sink function method, this paper develops a seepage model of multi-fractured horizontal well incorporating stress-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
(21 reference statements)
0
3
0
Order By: Relevance
“…It is shown that HF length only affects the early flow regimes, including the skin effect transition flow regime, the linear flow regime within HFs, and the early radial flow regime. As the HF length is decreased, pressure drop and pressure derivative curves are shifted upwards (Chen et al, 2016;2Chen et al, 2017a;Cao et al, 2018). With the decrease of HF length, the duration of linear flow regime within HFs becomes short.…”
Section: Effect Of Hydraulic Fractures Permeability Modulusmentioning
confidence: 99%
See 2 more Smart Citations
“…It is shown that HF length only affects the early flow regimes, including the skin effect transition flow regime, the linear flow regime within HFs, and the early radial flow regime. As the HF length is decreased, pressure drop and pressure derivative curves are shifted upwards (Chen et al, 2016;2Chen et al, 2017a;Cao et al, 2018). With the decrease of HF length, the duration of linear flow regime within HFs becomes short.…”
Section: Effect Of Hydraulic Fractures Permeability Modulusmentioning
confidence: 99%
“…In addition, skin effect and wellbore storage can be introduced into transient-solution directly in the Laplace domain (Cao et al, 2018),…”
Section: Coupling Matrix/natural Fractures and Hydraulic Fracturesmentioning
confidence: 99%
See 1 more Smart Citation